Training of "Implementasi Kurikulum Merdeka (IKM)" Through in House Training (IHT) For 21st Century Prospective Teacher Student Communities - Anjarwati, Ani; Ribut Prastiwi Sriwijayanti; Isyuniandri, Dzaky; Putri Fatimattus Az Zahra; Zahro Aulia, Uul (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract: Curriculum is the heart of education. In its implementation it underwent various changes. As aprospective teacher, every change in the curriculum is necessary, so it is very important to deepen yourknowledge regarding the preparation of curriculum components as a preparation before entering theelementary school environment. Wokrhsop Implementation of the Independent Curriculum (IKM) whichis carried out through In House Training (IHT) is a learning tool for prospective teachers to equipthemselves in understanding the components of the Independent Curriculum, namely LearningAchievements (LA), Learning Objectives (LO) and Learning Objective Flow (LOF) . The IKM Workshopwas carried out in several stages, namely (1) observing the condition of the participants; (2) making activity proposals, flyers and distribution; (3) inviting external sources; (4) pretest; (5) Implementation of IKM activities; (6) Completing the post-test. The results obtained after implementing the IKM workshop showed an increase of 91.1% of participants who were able to understand and develop the IndependentCurriculum components, namely Learning Achievements (CP), Learning Objectives (TP) and LearningObjective Flow (ATP).